Determinants of Adolescent Buprenorphine/Naloxone Abuse - Anwar, Samsul; Azman, Azlinda; Jamir Singh, Paramjit Singh (Asian Social Work Journal, 2025)
Street heroin completely disappeared from the black market in 2019 in Bandung, Indonesia. This situation occurred because many heroin abusers switched to the more readily available and cheaper buprenorphine/naloxone. The purpose of this study was to analyze the factors that encourage adolescents to engage in buprenorphine/naloxone drug abuse. Qualitative methodology with a phenomenological approach was used. In-depth interviews were conducted from September to November 2021 with 13 male and 4 female students as informants. The research findings showed that all research informants had a history of drug abuse since elementary and middle school. Before being addicted to buprenorphine/naloxone, informants were already addicted to drugs, some were even at the level of hardcore addiction or severe addiction. Factors that encouraged informants to abuse drugs included a negative environment at home, among friends and school, and ineffective communication between children and parents. In everyday life, apart from peers, informants also have older friends who have a negative influence. Informants also have low self-control as indicated by drug taking.